Current applications of cardiac troponin T for the diagnosis of myocardial damage - Vasatova, Martina; Pudil, Radek; Horacek, Jan M; Buchler, Tomas (Advances in clinical chemistry, 2013)
Biochemical markers of myocardial injury play an important role in the diagnosis of cardiovascular diseases. Measurement of cardiac biomarkers is one of the most important diagnostic tests in acute myocardial infarction (AMI), heart failure, and other cardiovascular disorders. Recently, the European Society of Cardiology, the American College of Cardiology Foundation, the American Heart Association, and the World Heart Federation have published a consensus definition of AMI that includes a detailed guideline for the assessment of biochemical markers in suspected disease. The cardiac troponins (cTI and cTnT) were recommended as preferred markers of myocardial necrosis in this setting. Herein, we review cardiac troponin biochemistry, the performance characteristics of cTnT assays, and optimal utilization of troponin in patients with proven or possible cardiovascular disease. We also discuss the use of troponin tests, with emphasis on cTnT, in different clinical situations in which its levels may be elevated.
Keywords: protein - isoformy; troponin T; myokard; kardiovaskulární nemoci; Protein Isoforms; diagnostické techniky kardiovaskulární; Animals; Diagnostic Techniques, Cardiovascular; Humans; biologické markery; Cardiovascular Diseases; Myocardium; Troponin T; lidé; Biomarkers; zvířata